Organizational learning, the learning organization and adult education - Matthias Finger; Diana Woolis (Adult Education Research Conference, 1994)
In this paper we will present and critically analyze the literature on organization learning and the learning organization. After recalling the historical context of the emergence of these two concepts, their conceptual differences will be clarified. The main portion of this paper will identify and discuss the five schools of thought that deal today with organizational learning and the learning organization. We will point out the main weaknesses of each of these schools and derive, from there, the challenges for adult education.